IMPLEMENTATION OF SCHOOL LITERACY MOVEMENT IN ELEMENTARY SCHOOLS - Ansori Ansori (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
This study aims to obtain information about the implementation of GLS or School Literacy Movement in Cluster 01 Elementary School, Pujer District, Bondowoso Regency. This research uses qualitative research type with case study research design. The data collection techniques used are observation, interviews and documentation. The results showed that the implementation of the School Literacy Movement in Cluster 01 Elementary School Pujer District is still at the habituation stage, namely 1) through reading aloud activities for approximately 15 minutes before learning for low grades and heart reading for high grades, 2) creating reading corners in each class, and 3) providing school library facilities. In implementing the School Literacy Movement, there are still several obstacles, including: 1) there is still a lack of reading books; 2) lack of interest in reading students; 3) the teacher has not fully carried out this activity; 4) lack of guidance from the local education office on the School Literacy Movement; 5) as well as parents who are somewhat indifferent to the needs of children in order to support the School Literacy Movement. Meanwhile, efforts to overcome obstacles during the implementation of the School Literacy Movement are: 1) seeking the fulfillment of reading books and library facilities by allocating School Operational Assistance (BOS) funds; 2) SDN Kejayan 1 frees students to choose whenever students want to read, not necessarily in the 15 minutes pre-learning so that a carpet is provided in the reading corner for them to use as a seat pad when they want to read; 3) SDN Kejayan 1 in order to improve the quality of GLS implementation by discussing and collaborating with other schools on occasions when gathering at Teacher Working Group activities in cluster 01 and Principal's Working Group (KKKS) or to other schools that are also GLS reference schools.